Green Accounting and Firm Performance: A Systematic Literature Review of Empirical Evidence in Accounting Literature - Frasetyo Angga Saputra; Djaddang, Syaril; Widiastuti, Tri; Amar, Nurmala (Lembaga Teewan Journal Solutions, 2026)
This study systematically reviews empirical evidence on the relationship between green accounting and firm performance in accounting literature. The topic is increasingly important as firms are expected to provide credible, measurable, and decision-useful environmental information, particularly when climate change, resource efficiency, emission disclosure, and sustainability are incorporated into corporate performance assessment. This study adopts a Systematic Literature Review approach guided by PRISMA 2020. Literature is searched through academic databases and journal indexes relevant to accounting, business, finance, and sustainability using keywords such as green accounting, environmental accounting, environmental management accounting, carbon accounting, firm performance, financial performance, firm value, ROA, ROE, and Tobin’s Q. Eligible articles are evaluated based on topic relevance, empirical orientation, methodological quality, green accounting proxies, performance indicators, and clarity of findings. The synthesis indicates that green accounting tends to be positively associated with firm performance through cost efficiency, reputation, regulatory compliance, green innovation, environmental performance, and disclosure quality. Nevertheless, empirical findings remain mixed due to differences in proxies, industry contexts, regulatory pressure, time horizons, and country-level characteristics. This study contributes by mapping measurement patterns, empirical directions, research gaps, and future research agendas in green accounting and firm performance research.